Anesthetic management for emergency cesarean delivery in parturient with achondroplasia - A case report and review of the literature - Youssef Motiaa; Wafae El Otmani; Zakaria Ouassou; Khalid Azizi (Wolters Kluwer Medknow Publications, 2020)
Achondroplasia is a genetic disorder where there is underdevelopment and shortening of the long bones formed by endochondral ossification without abnormalities of cartilage formation. Patients with achondroplasia can exhibit various manifestations: spinal abnormalities; thorao-lumbar kyphoscoliosis, respiratory and cardiac abnormalities; obstructive sleep apnea; and changes of the head and the midface. In women with achondroplasia, cesarean delivery is inevitable because the pelvis is invariably small. Anesthetic management for cesarean section in this population is controversial; the choice of anesthetic technique depends on the benefits and risks of each technique. Emergency cesarean is another factor to consider for the choice of anesthetic technique. We report the case of a 34-year-old Moroccan primipara with achondroplasia who had a cesarean delivery under Spinal anesthesia. Other possible anaesthetic techniques used for cesarean sections in such patients are also discussed.